PENGELOLAAN PEMBELAJARAN IPA MELALUI PENERAPAN METODE DEMONSTRASI PADA SISWA KELAS IV SD - Sudarti Sudarti (Manajer Pendididikan, 2017)
The purpose of this study was to determine the increased understanding of the concept of sound energy sources in the fourth grade students of State Elementary School 09 Kepahiang through the management imposed a method of learning science by demonstration. This type of research is a classroom action research. The results show that efforts to guide students seek remedy science concepts through demonstrations and group work method makes students more active in learning activities. Students can demonstrate props so it is easy to understand the concept of sound energy source. Final test results indicate an increase, which is the first cycle of the average value of students 45 with mastery learning 45%, the second cycle the average value of students 75 with mastery learning 75%, and the third cycle the value of the average student 95 with learning completeness 95%.